MODIFIED AES APPROACHES IN ENCRYPTION AND DECRYPTION FOR INSECURE ENVIRONMENT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The security of video applications such as commercial videos, military videos and others have become animportant field of research recently. One of the most secure algorithms is Advanced Encryption Standard(AES) algorithm;however this algorithm is inefficient for dealing with video encryption due to itsslowness property. This paper proposes a new modified of AES to make it more suitable for encryptingdigital video. The Modification focuses on the slowest transformations in original AES which is mixcolumns transformations and replace them with new Henon map chaotic based mask and one mixcolumns transformation. Resulting in a significant reduction in encryption and decryption time andenhance the security level of AES algorithm, and also the key space is increased as observed in thesimulation results of proposed system.